The TMEn, Proximate Analysis, Amino Acid Content and Amino Acid Digestibility of Glandless and Commercial Cottonseed Meal for Broilers - Salas, C.; Ekmay, R.; England, J.; Cerrate, S.; Coon , C.N. (International Journal of Poultry Science, 2013)
Cotton seed meal (CSM) is an alternative ingredient in poultry diets but its use is limited due to the presence of gossypol and the potential effects of gossypol on digestibility of nutrients. Glandless cottonseed is available and contains very low gossypol but there has been a limited amount of poultry nutritional studies completed with glandless cottonseed meal (GCSM). The TMEn, proximate analysis, amino acid content and amino acid (AA) digestibility of a glandless (GCSM) and a commercial (CCSM) cottonseed meal were determined with broilers. Thirty 42-day old Cobb 500 male broilers were precision-fed 30g of CCSM, GCSM and glucose and excreta collected during a 48 h period. Glucose was fed to serve as a control (no nitrogen or AA content). The chemical composition, gossypol content, True metabolizable energy (TMEn) and digestibility coefficients for AA were calculated for both meals. The crude protein and fat content of GCSM was higher than the CCSM (54 and 51%, 6 and 2%, respectively). Both meals were similar in calcium, total phosphorus and phytic acid contents. The CCSM had a higher content of total and free gossypol (1.52 and 0.161%, respectively) when compared to GCSM (0.02 and .003%, respectively). The TMEn for the GCSM provided approximately one thousand kcal more per energy/ kg than the CCSM. The essential AA content (g/kg; 90% DM) was determined for both cottonseed meals and was generally higher for GCSM compared to CCSM but both types of CSM contained higher levels of key essential AA than reported values for AA in the literature. The most extreme differences were for methionine and cystine; % methionine content was approximately 2 fold higher than values in the literature and the % cystine was 74 to 93% higher. The true digestibility coefficients for essential AA ranged from the low of 73.9% for isoleucine to 91.8% for arginine, for CCSM; the amino acid digestibility coefficients for GCSM were all higher than 90% for the essential AAs.